Diseño y construcción de una máquina embaladora de cajas para material ferretero en la empresa Casa Importaciones de la ciudad de Ambato”. - Jijón Izurieta, Carlos Alexis (2022)
The actual technological proposal has as aim to design and build a packaging machine for cardboard boxes, through a technical analysis, this project has been developed based on the material hardware Casa Importaciones enterprise need and requirements, located into Tungurahua Province, Canton Ambato, Huachi Chico neighborhood, it bases into problem of making the packing boxes process an artisanal way, through the workers force use, in the national and international market, there are machines, what make the same process, whose have very complex mechanisms, therefore, they have an elevated value. The proposal proposes a machine design, what fulfills the same purpose using simple mechanisms with a lower economic investment, by allowing small enterprises have access it. With the application this project, the direct beneficiaries are the owner and the workers said enterprise. The machine design focuses onto a semi-automatic packaging system, at taking as a reference, by a field research, the cardboard boxes required weight and maximum volume to be packed, being 20 kg, weight and 275〖cm〗^3volume, which sits onto a rotating plate with a 20 rpm speed, it has a vertical stretch film reel-holder support, what is manipulated by the machine operator. The machine general system is made up two systems, both mechanical and electrical, by which are made element calculations, what compose the machine and with the Inventor 3D engineering software help are related and checked the mechanical stresses, such as: tension, bending and the safety factor into machine design. According to the got calculations, they are attached the materials and standardized elements acquired from a pedestal drill said enterprise, therefore, the speed transmission ratio is calculated based on the got pulleys diameters from drill, in front of referenced it performs a pulley game mechanism for reducing the motor speed with the a frequency variator helps to stabilize the said motor input speed. The machine is conform for a machined parts packaging set, so that can be developp efficiently, with this implementation, it is considered an important development into enterprise, since could be made mechanically, optimizing time, and therefore, in the Electromechanical Engineering field is considered as a solution to small enterprises problems, since it treat an electrical machine with industrial purposes. Finally, it was set a cost study, so that, the designed machine is local market part.